Viruses : essential agents of life - Witzany, Gunther (Dordrecht : Springer, 2012)
A renaissance of virus research is taking centre stage in biology. Empirical data from the last decade indicate the important roles of viruses, both in the evolution of all life and as symbionts of host organisms. There is increasing evidence that all cellular life is colonized by exogenous and/or endogenous viruses in a non-lytic but persistent lifestyle. Viruses and viral parts form the most numerous genetic matter on this planet.
Includes bibliographical references and index.
Keywords: Viruses; Viral genetics; Virology; Electronic books